Modeling and Forecasting Infections, Fatalities and Recoveries from COVID-19 pandemic in SSA: A case of the 10 hotspot in Sub-Saharan Africa - Momodou Mustapha Fanneh; Mustapha Jobarteh; John T. Mendy; Amadou Jawo (Technium Social Sciences Journal, 2020)
This paper aims to model COVID 19 infections and fatalities and how the growth paradigm of the continent will shift overtime. The study used epidemiological data of countries and two mathematical models, i.e., Logistic model growth model and modified growth model to predict number of patients (infections), number of deaths and number of recoveries from COVID-19 in the continent. In this study, it is showed that with the current state of the spread of the COVID19, it is projected that the number of infections will reach 141,733 in the next 30 days and 986,059 patients in the next 60 days. Also, 12,972 will die in the next 30 days and 151,190 in the next 60 days and 73,590 will recover in the next 30 days and 490,547 in the next 60 days. These estimates will help countries to strengthen their policies towards COVID-19 such as lockdown, social distancing, wearing of face masks, washing of hands with water and soap and using hand sanitizers.